Comparison Of The Drop Weight Impact Performance Of Sandwich Panels With Aluminium Honeycomb And Titanium Alloy Micro Lattice Cores - Rafidah, Hasan; Mines, Robert; Shen, Eva; Tsopanos, Sozon; Cantwell, Wesley; Brooks, Wesley; Sutcliffe, Chris (Trans Tech Publications, 2010)
This paper is a study of the drop weight impact behaviour of small sandwich panels of carbon epoxy skins with aluminium honeycomb and titanium alloy micro-lattice cores. A series of experimental tests have shown that the specific impactor penetration behaviours are similar for both cores. The reasons for this are a result of the detailed deformation and rupture behaviour of the two types of core. The deformation and rupture mechanisms of honeycomb and micro-lattice structures will be discussed in general terms, and these observations will be used to inform discussion of actual deformation and rupture in the panel tests. In this way, micro energy absorbing mechanisms will be related to panel performance, and conclusions on the way forward for improved penetration performance using other core materials and geometries will be identified.